How to Start a Food Business: Basic Food Technology: Food Acidity - Soohyoun Ahn; Jayna Goldstein; George Baker; Matthew Krug (EDIS)
Food acidity is an important parameter in food product development. Most people know that food acidity influences flavor, but more importantly, food acidity can affect the ability of microorganisms to grow in food. Food acidity, or the amount of acid that is present in the food, is used to classify a food product, and that classification determines the regulatory requirements for the specific food product. This new 6-page publication of the UF/IFAS Food Science and Human Nutrition Department describes how to measure food acidity and how food is classified based on its acidity. Written by Soohyoun Ahn, Jayna Goldstein, George Baker, and Matthew Krug. https://edis.ifas.ufl.edu/fs325